Professional Constructs of Future Teachers in Special Education within the Context of Remedial Guidance for Adults with Minimal Schooling - Correa Molina, Enrique; Villemagne, Carine (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2011)
The role of teachers today in special education requires extensive background knowledge about various types of learners, their specific needs and the particularities of the stakeholders with whom the teacher is called to collaborate. The knowledge constructed by future teachers is acquired not only in the formal context of initial training, but also in the field, in contexts other than the purely academic milieu. In this frame, the implementation of practical activities involving the application of diverse knowledge has its place in a training curriculum. This is the case of the clinic activity referred to in this article.